MATHEMATICAL MODELLING OF THE PHYSICAL PROPERTIES OF ENERGY CARRIERS IN THE BIOGAS PRODUCTION SYSTEM - Hryhorskyi, S. Ya.; Zapukhliak, V. B.; Voznyі V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
The article discusses the topical issue of mathematical modelling of the physical properties of energy carriers in grain distiller’s grains biogas production systems. The efficiency of biogas technologies largely depends on the accurate design and operation of systems for transporting raw materials and the biogas produced. The main objective of the work is to develop mathematical models of the key physical properties (density, dynamic viscosity, coefficient of volume expansion, specific isobaric heat capacity and thermal conductivity coefficient) of grain distiller’s grains, industrial effluents and biogas. For grain distiller’s grains, the models are developed based on laboratory studies and take into account the dependence of properties on temperature and mass concentration of dry substances. For industrial wastewater, a 4% caustic soda solution is taken as the base liquid. Modelling of biogas properties is based on its component composition. The developed models are the basis for performing thermohydraulic calculations, optimising the design and operation of pipeline systems in biogas plants, which contributes to increasing their reliability, safety and economic feasibility.